Energy Drinks: A Public Health Perspective - Nikolaos Nikitidis (Research Highlights in Disease and Health Research Vol. 8, 2023)
The aim of this study is to assess the potential risks of using energy drinks (EDs) by athletes and exercisers. To accomplish this, we assess the consumption and the level of knowledge of the consumers as unawareness can cause hazardous behaviors. Furthermore, an investigation is being conducted on the proper public health protection measures. A specifically designed questionnaire was used for this study. There were 234 athletes and exercisers in the sample. In order to be accepted, participants must complete a training session once every seven days. The level of consumption measured (35.5%) is in accordance with the literature. Advertising is the main source of knowledge (69.2%), although it does not ensure reliable information. Consequently, while exercisers and athletes believe they have sufficient understanding on the subject (91.2%), in reality this is not accurate (the knowledge score is 10.12/18). Due to their lack of awareness, a large number of them are combining energy drinks with alcohol, which is a hazardous activity. It has been strongly recommended that better public education (96.6%) as well as more information on product labels (94.8%) should be implemented in order to handle Eds issues. Additionally, 61.5% of respondents suggested that there should be restrictions on EDs advertising. In conclusion, it is evident that the majority of the population supports the implementation of laws that limit the amount of primary ingredients of ED.